Cerebellar Direct Current Stimulation (ctDCS) for the treatment of Phantom Limb Pain (PLP). Issue 1 (January 2019) - Bocci, T.; De Carolis, G.; Mansani, F.; De Rosa, A.; Ferrucci, R.; Priori, A.; Valeriani, M.; Sartucci, F.
Abstract : The aim of this study was to evaluate the possibility to modulate pain perception with cerebellar transcranial Direct Current Stimulation (ctDCS) in phantom limb pain (PLP). Patients underwent ctDCS (anodal or sham, 2.0 mA, 20' per day, five days a week). Clinical scores (VAS) and electrophysiological parameters (Laser Evoked Potentials, LEPs) were assessed before tDCS, at the end of 5-days treatment, two weeks and one month after ctDCS completion. LEPs were obtained using a Nd:YAP laser (wavelength 1.04 μm, pulse 164 duration 2–20 ms). The amputated limb was stimulated by laser pulses with short duration (5 ms) and small diameter spots (5 mm). Anodal tcDCS reduced non-painful phantom limb sensations (p < 0.001) and paroxysmal pain (p = 0.042), with effects lasting for three weeks after protocol completion. Concurrently, anodal polarization significantly dampened LEP amplitudes (N1: p = 0.021 and N2/P2: p = 0.0034). ctDCS significantly improved both painful and non-painful phantom limb sensations. Cerebellar polarization may be useful for the treatment of pain syndromes; ctDCS may act not only on spinal nociceptive neurons, but also on wide-range cortical networks of the pain matrix, influencing LEPs and pain experience through top-down and bottom-up mechanisms.